2010
DOI: 10.1016/j.ajo.2009.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded Protein Response in Fuchs Endothelial Corneal Dystrophy: A Unifying Pathogenic Pathway?

Abstract: Purpose To assess for activation of the unfolded protein response in corneal endothelium of Fuchs endothelial corneal dystrophy patients. Design Retrospective comparative case series of laboratory specimens Methods Corneal specimens of patients with Fuchs dystrophy and controls with corneal pathologies other than Fuchs dystrophy were evaluated by transmission electron microscopy (TEM) to evaluate for structural changes of the rough endoplasmic reticulum in corneal endothelium. TEM images were evaluated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 25 publications
5
66
0
Order By: Relevance
“…17 The thickened Descemet's membrane and excrescences comprise several ECMs such as collagen types I, IV, and VIII; fibronection; and laminin-these were considered to be secreted by affected CECs. 14 Since small sample size obtained from FECD patients is an obstacle for researchers, 11 we established an in vitro cellular model of FECD by immortalization of the CECs received from late-onset FECD patients. The data presented in this study identified potential overexpressed ECM proteins, which include collagen type I and fibronectin at both mRNA and protein levels and probably contribute to the excessive ECM deposition found in Descemet's membrane in FECD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The thickened Descemet's membrane and excrescences comprise several ECMs such as collagen types I, IV, and VIII; fibronection; and laminin-these were considered to be secreted by affected CECs. 14 Since small sample size obtained from FECD patients is an obstacle for researchers, 11 we established an in vitro cellular model of FECD by immortalization of the CECs received from late-onset FECD patients. The data presented in this study identified potential overexpressed ECM proteins, which include collagen type I and fibronectin at both mRNA and protein levels and probably contribute to the excessive ECM deposition found in Descemet's membrane in FECD.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the molecular mechanisms of excessive ECM production as a possible cause of ER stress 11 in CECs in FECD. For this purpose, we established an FECD cellular in vitro model using immortalized cell lines derived from FECD and control patients.…”
mentioning
confidence: 99%
“…Oxidative stress and apoptosis are reported to play a role in the development of FECD particularly in regard to accelerated corneal endothelial cell loss (Borderie et al 2000;Li et al 2001;Buddi et al 2002;Szentmáry et al 2005;Engler et al 2010;Jurkunas et al 2010;Azizi et al 2011). This may be in part due to chronic ultraviolet (UV) light exposure (Inoki et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Both association and linkage studies showed that a polymorphism in the transcription factor 4 (TCF4) gene was associated with FECD (Baratz et al 2010;Li et al 2011). Apoptosis was shown to be involved in the pathogenesis of KC and FECD (Mohan et al 1997;Cho et al 1999;Kim et al 1999;Borderie et al 2000;Li et al 2001;Kaldawy et al 2002;Gottsch et al 2003;Szentmáry et al 2005;Joyce et al 2009;Engler et al 2010;Jurkunas et al 2010). It was also shown that the FAS/FASLG system is expressed in the cornea and might have important functions in normal corneal physiology and in the pathophysiology of corneal diseases, including modulation of keratocyte apoptosis after epithelial injury (Wilson et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…However, this theory would agree with aberrant protein expression, which is one of the consequences of oxidative stress-induced damage. 51 Wound healing patterns of the normal and FECD corneal endothelium Until recently it was thought (as endothelial cells were believed to have no regenerative potential) that when a corneal cell is 'lost', it induces a wound healing response where the defect of the lost cell is covered by an adjacent endothelial cell through migration and elongation. 13 However, a recent study by He et al, 40 suggested that the corneal periphery contains a reservoir of stem-like cells that replace damaged or dead endothelium by continuous centripetal migration patterns (Figures 1b and c).…”
Section: Pathophysiology Of Fecdmentioning
confidence: 99%